Tafsir Ayat Tentang Kesatuan Agama Perspektif Al-Habasyi - Asyhari (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
The concept of religious unity is a controversial theme among Muslims. Because in general Muslims believe that Islam is the only true religion, besides Islam is a false religion. Those who base their opinion on Q.S Ali Imran: 64. Abdullah al Habashi rejects the claim that this verse shows the unity of religion, with the understanding that all religions are the same, but he emphasizes that the religion of all the prophets is the same, namely Islam. Based on this description, it is interesting to study al Habashi's interpretation of Q.S Ali Imran: 64, so that a problem is formulated, how is the interpretation of the verse of religious unity in al Habashi's perspective?. To answer the formulation of the problem, the author uses the method of library research (library research). The author describes the opinion of al Habashi about the verse of religious unity. This study resulted in a conclusion that according to al-Habashi, Q.S Ali Imran: 64 does not mean an invitation to find common ground, ignoring existing differences. But according to him, the sentence